How do diverse low-income and middle-income countries implement primary healthcare team integration to support the delivery of comprehensive primary health care? A mixed-methods study protocol from India, Mexico and Uganda - Rohina Joshi; Innocent Besigye; Ileana Heredia-Pi; Manushi Sharma; David Peiris; Robert James Mash; Hortensia Reyes-Morales; Felicity Goodyear-Smith; Renu John; Doris Ortega-Altamirano; Emanuel Orozco-Nunez (BMJ Open, 2022)
This study aims to understand PHC team integration, composition and organisation in the delivery of CPHC in India, Mexico and Uganda.
Keywords: Energy poverty; Human health and well-being; Per capita energy use; Sustainable development goals